(3QSGdI aj GdbOQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3QH CYf gPg QSGdI GdTjN GdQFjS YHO Gddg Hf SjfG ai GdbOQ MGWce Gddg LeGYI GdENhGf ef EdGShGA hGSHZ Ydjce LSGFe GdCdGA Gfg HJSJQ YhQJi s
(3BNQgG (B:s
(3hQhOg CSdGg hGdLgI cGf bOQ ahb EdG haQM NjGdkG hWGQ MOjKkG hQaY hbJkG efgRekG jhe GdSGHY hGdYTQjf ef Pi GdMLI SfI KdGK hYTQjf hCQHYeGFI hcCfi Hg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdJhMjO hGdedd hGdfMds